PELAKSANAAN TUGAS KEPALA DESA DALAM PEMBANGUNAN DESA SEBADAI HULU KECAMATAN BUNGURAN TIMUR LAUT KABUPATEN NATUNA - Nendra Ilyadi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
NENDRA ILYADI, 1001120291. Execution of Tasks in a Village Head Village Development Districts Sebadai Upstream Bunguran Northeast District Natuna. guided by Dra. Ernawati. M. Si.Village head as formal leaders in village governance plays an important role in determining the successful implementation of development, especially at the village level. Execution of tasks in rural development can not be separated from the village chief leader figure. Strategic position as an element owned by the village chief in village administration leader who is the central point and the dynamic factor or that embody the entire course of growth and governance activities of the village.Purpose of this study is to investigate the implementation of tasks in a village head village development districts sebadai upstream Bunguran northeast district Natuna and the factors that hinder the implementation of tasks in a village head village development districts sebadai upstream Bunguran northeast district Natuna. To analyze the phenomenon in this study the authors used the theory Winardi the right time utilization indicator, the number of outputs, willingness to cooperate, and the quality of work. Methodology used in this study was a qualitative study using purposive sampling and snowball sampling.The results of this study demonstrate the implementation of tasks in a village head village development districts sebadai upstream Bunguran northeast district Natuna still not optimal. As for the factors found are communication, resources and attitudes, whether from internal or external head of the village and community.keywords: Implementation of the village chief task